Burkholderia paludis sp. nov., an Antibiotic-Siderophore Producing Novel Burkholderia cepacia Complex Species, Isolated from Malaysian Tropical Peat Swamp Soil - Ong, Kuan Shion; Aw, Yoong Kit; Lee, Learn Han; Yule, Catherine M.; Cheow, Yuen Lin; Lee, Sui Mae (Frontiers in Microbiology, 2016)
A novel Gram negative rod-shaped bacterium, designated strain MSh1T, was isolated from Southeast Pahang tropical peat swamp forest soil in Malaysia and characterized using a polyphasic taxonomy approach. The predominant cellular fatty acids (>10.0%) were C16:0 (31.7%), C17:0 cyclo (26.6%) and C19:0 cyclo w8c (16.1%). The polar lipids detected were phosphatidylglycerol, phosphatidylethanolamine and diphosphatidylglycerol. The predominant ubiquinone was Q-8. This revealed that strain MSh1T belongs to the genus Burkholderia. The type strain MSh1T can be differentiated from other Burkholderia cepacia complex (Bcc) species by phylogenetic analysis of 16S rRNA gene sequence, multilocus sequence analysis (MLSA), average nucleotide identity (ANI) and biochemical tests. DNA-DNA relatedness values between strain MSh1T and closely related type strains were below the 70% threshold value. Based on this polyphasic study of MSh1T, it can be concluded that this strain represents a novel species within the Bcc, for which the name Burkholderia paludis sp. nov. is proposed. The type strain is MSh1T (=DSM 100703T =MCCC 1K01245T). The dichloromethane extract of MSh1T exhibited antimicrobial activity against four Gram positive bacteria (Enterococcus faecalis ATCC 29212, Enterococcus faecalis ATCC 700802, Staphylococcus aureus ATCC 29213, Staphylococcus aureus ATCC 700699) and a Gram negative bacteria (Escherichia coli ATCC 25922). Further purification work has led to the isolation of Compound 1, pyochelin. Pyochelin demonstrated antimicrobial activity against four S. aureus strains and three E. faecalis strains with MIC values of 1.57 µg/ml and 3.13 µg/ml respectively. SEM analysis showed that the cellular morphology of E. faecalis ATCC 700802 was not affected by pyochelin; suggesting that it might target the intracellular components. Pyochelin, a siderophore with antimicrobial activity might be useful in treating bacterial infections caused by S. aureus and E. faecalis, however further work has to be done.